2010
DOI: 10.1007/s10534-010-9337-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Deferasirox for removal of cadmium ions in rat

Abstract: An investigation was conducted to evaluate the ability of Deferasirox (ICL670 or Exjade) following the distribution of cadmium salt in male Wistar rats. Cadmium was introduced to several groups of weanling male Wistar rats through different means, by act of drinking, feeding. A control group was fed on a diet containing normal level of iron. After a period of 30 days, all the rats administered cadmium were severely anemic and showed toxicity symptoms through loss of hair and increasing in cadmium and reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In our previous experiments on rats we investigate the chelation potency of Deferasirox given to animals after cadmium and thallium loading. Our results showed that cadmium and thallium concentrations increase in blood serum after their administration while the iron level decreases, therefore it can cause iron deficiency anemia [4,5]. Anemia is a pathologic process in which the hemoglobin (Hb) concentration in red blood cells is abnormally low.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous experiments on rats we investigate the chelation potency of Deferasirox given to animals after cadmium and thallium loading. Our results showed that cadmium and thallium concentrations increase in blood serum after their administration while the iron level decreases, therefore it can cause iron deficiency anemia [4,5]. Anemia is a pathologic process in which the hemoglobin (Hb) concentration in red blood cells is abnormally low.…”
Section: Introductionmentioning
confidence: 94%
“…Also at the end of this step, some hematological indices such as Hemoglobin (Hb) concentration in red blood cells, serum iron concentration, Total Iron Binding Capacity (TIBC), serum mercury concentration and etc. were determined [4,5].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Different compounds were tested in animal models as antagonists of Cd, but information regarding their effects on Cd-induced alterations in spleen function is still sparse (Blanuša et al, 2005;Nemmiche et al, 2007;Luchese at al., 2007;Gong at al., 2008;Shukla and Kumar, 2009;Manna et al, 2009;Fouad at al., 2009;Sinha et al, 2009;Flora and Pachauri, 2010;Chlebda et al, 2010;Saljooghi and Fatemi, 2010;Sinicropi et al, 2010). Our recent studies demonstrated that monensin (a polyether…”
Section: Demonstrated That This Metal Inhibited Cell Proliferative MImentioning
confidence: 99%
“…This conclusion might be more convincing if they had administered the DMSA a number of months following Cd exposure, so that the Cd in the mice had had time to be fully sequestered in the intracellular pools (largely metallothioneinbound) where most Cd is found during chronic low-level exposure. In any case, it would probably be appropriate to conduct clinical studies to assess whether prolonged oral protocols of DMSA (or perhaps other orally administrable agents capable of chelating Cd [102]) might have a worthwhile impact on Cd body burden in patients with excessive Cd levels. Certain ester derivatives of DMSA (such as the monoisoamyl ester) have greater cell permeability, and can promote excretion of metallothionein-bound Cd in mice [103,104]; unfortunately, these agents have never been approved for clinical use, and may have more toxic potential than well-tolerated DMSA [105].…”
Section: Chelation Therapy May Have Limited Potential In Chronic Cadmmentioning
confidence: 99%